KOMPOSISI DAN STRUKTUR VEGETASI HUTAN MANGROVE DI KELURAHAN TAMPO KECAMATAN NAPABALANO KABUPATEN MUNA - abdul sakti; Sahindomi Bana; Nurhayati Hadjar; La de Ahmaliun; Arniawati arniawati; sarwinda intan putri (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2024)
This study aims to identify the composition and structure of mangrove vegetation and measure species diversity in Tampo Village, Napabalano District, Muna Regency, Southeast Sulawesi. Data collection was carried out by the plotted line method, using transects from the sea to the mainland. The parameters analyzed included density, frequency, and dominance which were then used to calculate the Important Value Index (INP) and the Shannon-Wiener Diversity Index (H'). The results showed species diversity at varying growth rates, from low to moderate, with the type Avicennia sp. show significant dominance. The H' diversity value ranged from 0.60 to 2.02, indicating that the habitat was in a stable condition without major constraints. The tree's life tier has good ecosystem resilience, allowing for quick recovery after disturbances. Species dominance Avicennia sp. indicates strong adaptability and competitiveness in the local environment, which plays an important role in ecosystem stability. These findings highlight the importance of sustainable management of mangrove ecosystems to protect biodiversity and coastal ecosystems in the region